Knowledge, perceptions and attitudes of radiologists and nuclear medicine physicians towards medical teleimaging in French-speaking sub-Saharan Africa - Adambounou, Kokou; Kouevidjin, Beleave; DJIGO, Salif; Degan, Romaric; Houndetoungan, Gilles David; Ouedraogo, Ali (My University, 2025)
Background: The successful development of teleimaging platforms depends on imaging physicians’ knowledge, perceptions and support, but few studies have focused on this specific subject in Africa. The objective of this study is to assess the knowledge, perceptions and attitudes of radiologists and nuclear medicine physicians towards medical teleimaging in French-speaking sub-Saharan Africa. Materials and methods: This cross-sectional study was conducted from 5 May to 5 August 2022 and included radiologists and nuclear medicine physicians practising in French-speaking sub-Saharan African countries. Data were collected electronically via Google Forms. Results: Of the 141 imagers surveyed, 7.1% were nuclear medicine physicians, 65.96% had already received training in teleimaging, and 9.93% had already carried out formal teleimaging activities. Of the respondents, 44.68% were familiar with both primary teleimaging procedures (telediagnoses and tele-expertise), 51.06% had some knowledge of Picture Archiving and Communication Systems (PACS) and Digital Imaging and Communications in Medicine (DICOM), and 84.4% knew that patient consent was required before telediagnosis. Approximately one quarter were unaware that the presence of a nuclear medicine physician was mandatory for remote diagnosis in nuclear medicine, and 51.1% had no idea of the technical specifics of a computer dedicated to teleimaging. The majority (92.90%) perceived teleimaging as having more advantages than disadvantages, and 98.6% used virtual channels such as WhatsApp to transfer images. In 56.02% of the cases, they did not take any security precautions when performing teleimaging procedures. Conclusion: The level of knowledge of teleimaging among imaging physicians in French-speaking sub-Saharan Africa was relatively unsatisfactory, although the perception was encouraging, and the right attitudes were not always adopted.
Keywords: Teleimaging; Radiologists; Nuclear medicine physicians; Telemedicine; French-speaking sub-Saharan Africa